Lactobacillus gasseri PA-3 utilizes the purines GMP and guanosine and decreases their absorption in rats. (4th May 2018) - Yamada, N.; Saito, C.; Murayama-Chiba, Y.; Kano, H.; Asami, Y.; Itoh, H.
ABSTRACT: Excessive intake of purine-rich foods elevates serum uric acid levels, making it a risk factor for hyperuricemia. We hypothesized that lactic acid bacteria ingested with food might utilize purines and contribute to their decreased absorption in the intestines, thereby preventing hyperuricemia. We previously reported that Lactobacillus gasseri PA-3 (PA-3) incorporates adenosine/inosine and related purines and that oral ingestion of PA-3 reduced the absorption of these purines in rats. However, it is unclear whether PA-3 also decreases the absorption of other purines, such as guanosine 5′-monophosphate (GMP) and guanosine. This study investigated whether PA-3 incorporates GMP and guanosine and reduces their absorption in rats. PA-3 incorporated both purines, with 14 C-GMP uptake being greater than that of 14 C-guanosine. Radioactivity in rat blood was significantly lower 30, 45, and 60 minutes after administration of 14 C-GMP plus PA-3 than after administration of 14 C-GMP alone and was significantly lower 15 minutes after administration of 14 C-guanosine plus PA-3 than after administration of 14 C-guanosine alone. PA-3 incorporates GMP and guanosine in vitro. Oral administration of PA-3 with GMP and guanosine reduces the intestinal absorption of these purines in vivo . These findings, together with those of previous studies, indicate that PA-3 reduces the absorption of major purines contained in foods. PA-3 may also attenuate the excessive absorption of dietary purines in humans, protecting these individuals against hyperuricemia.